The Influence of Roman Public Law on Contemporary Administrative Law - Sitek, Bronisław (PRAWO i WIĘŹ, 2025)
The subject of this study is to present the influence and impact of Roman public and administrative law on contemporary legal-administrative and institutional solutions. The organization of state administration is always flexible, meaning it adapts to changing political or social conditions. However, certain solutions are repetitive, and their legal and organizational structures are based on experiences and solutions which date back to ancient Rome. The research hypothesis is that many modern institutions within the structure of administrative bodies have their roots in institutions that functioned in Ancient Rome. Therefore, I used a descriptive method in the study, which allowed me to present Roman institutions with reference to contemporary solutions. In this respect, the work represents a novel contribution to both Polish and foreign literature. The study may also serve as an inspiration for contemporary administrative scholars to draw on the experiences of ancient states in their research.